2014
DOI: 10.2967/jnumed.113.129577
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Radiation Dosimetry of Deuterium-Substituted 18F-Fluoromethyl-[1, 2-2H4]Choline in Healthy Volunteers

Abstract: 11 C-choline and 18 F-fluoromethylcholine ( 18 F-FCH) have been used in patients to study tumor metabolic activity in vivo; however, both radiotracers are readily oxidized to respective betaine analogs, with metabolites detectable in plasma soon after injection of the radiotracer. A more metabolically stable FCH analog, 18 F-fluoromethyl-[1,2-2 H 4 ]choline ( 18 F-D4-FCH), based on the deuterium isotope effect, has been developed. We report the safety, biodistribution, and internal radiation dosimetry profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Should 18 F-fluoromethylcholine metabolism remain constant throughout the response-monitoring study, the performance of SUV AUC,WB , and to a lesser extent SUV, may be equivalent to SUV AUC,PP as a relative measure of response. Challapalli et al recently reported on a novel 18 F-labeled choline tracer that metabolizes less rapidly than 18 F-fluoromethylcholine, with parent fractions gradually decreasing to approximately 0.3 over the first hour after injection (25,26). With decreased interpatient variability in parent fractions, the performance of SUV and SUV AUC,WB may improve with respect to SUV AUC,PP .…”
Section: Discussionmentioning
confidence: 99%
“…Should 18 F-fluoromethylcholine metabolism remain constant throughout the response-monitoring study, the performance of SUV AUC,WB , and to a lesser extent SUV, may be equivalent to SUV AUC,PP as a relative measure of response. Challapalli et al recently reported on a novel 18 F-labeled choline tracer that metabolizes less rapidly than 18 F-fluoromethylcholine, with parent fractions gradually decreasing to approximately 0.3 over the first hour after injection (25,26). With decreased interpatient variability in parent fractions, the performance of SUV and SUV AUC,WB may improve with respect to SUV AUC,PP .…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that PET imaging of radiolabeled choline may be used to detect PDAC, provided there is adequate delivery of the probe, as the desmoplastic stroma in pancreatic cancers may impede its delivery (4). A recent study detected a relatively high uptake, but a low residence time, of a radiolabeled choline tracer in the pancreas of normal volunteers (30), suggesting that PDAC may be detected using relatively long-lived radiolabeled choline PET tracers that allow imaging at later time points to achieve good systemic clearance (30). …”
Section: Discussionmentioning
confidence: 99%
“…Bladder radioactivity, unlike other organs, was calculated, taking into account the bladder volume changes over the time course of the scan (12)(13)(14)(15). The effective dose (ED) was calculated using, first, the mean residence time over all subjects for each organ and, second, residence times for individual subjects with OLINDA/ EXM (version 1.1), which uses the organ weighting factors from ICRP 60 (16).…”
Section: Data Analysis Biodistribution and Dosimetrymentioning
confidence: 99%